Analysis of Mathematical Communication Skills Students for Two Variable Linear Equation Systems Material - Meli Susanti; Anisa Nurul Hasinah; Luvy Sylviana Zanthy (Department of Mathematics Education University of Muhammadiyah Malang, 2020)
The communication skills of eighth grade junior high school students are catergorized as low. The purpose of this study is to analyze and describe aspects of mathematical communication skill, the research subjects consisted of 10 class students in one of the private schools located in Cimahi. The research method with data collection techniques. From the descript test regarding the two variabel linear equation system of 4 question. The results of this study indicated that students mathematical communication skill are categorized as moderate with a percentage of 42.5 % with the percentage of each item, number one 47.5 %, question number two 60 %, and question number four 32.5 %.